PERSONALIZATION IN EMAIL MARKETING HOW TO INCREASE OPEN RATES AND ENGAGEMENT - Hojiakbar Muminov (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
Email marketing remains one of the most powerful tools for digital marketers, with a return on investment (ROI) that surpasses many other channels. However, the effectiveness of email campaigns hinges significantly on personalization. This article explores the critical role of personalization in email marketing, focusing on strategies to increase open rates and engagement. It delves into various personalization techniques, such as segmentation, dynamic content, behavioral triggers, and machine learning algorithms, that can be used to create highly targeted and relevant email experiences. Additionally, the article examines the impact of personalized email marketing on customer retention, loyalty, and overall marketing effectiveness. We also discuss the challenges associated with personalization, including data privacy concerns and the technical complexities of implementing advanced personalization strategies. Supported by over 20 scholarly references, this article provides a detailed, scientific exploration of how businesses can leverage personalized email marketing to drive engagement and maximize their ROI.